2011
DOI: 10.1007/978-3-642-24355-4_23
|View full text |Cite
|
Sign up to set email alerts
|

Technology Readiness Index (TRI) Factors as Differentiating Elements between Users and Non Users of Internet Banking, and as Antecedents of the Technology Acceptance Model (TAM)

Abstract: Abstract. The scope of this work covers the study of models developed for assessing critical aspects of consumer use and acceptance of technology-based products and services. We used the Technology Acceptance Model (TAM), and the Index of Readiness for the use of Technology (TRI) as theoretical references. We carried out field research on Internet banking users in order to: (1) evaluate the differences between the groups in terms of predisposition towards technology using the TRI model; and (2) test whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…This model aims to assist those responsible for implementing information systems to assess their current and future acceptance. There are studies that use TAM, for example, to evaluate the use and acceptance of word processor [22], to verify perceptions of compatibility between systems [35], to evaluate emotional reactions to the use of computers [19], to evaluate the use of productivity packages [16] and to support software producers who want to check the demand for new ideas and products [15].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 1 more Smart Citation
“…This model aims to assist those responsible for implementing information systems to assess their current and future acceptance. There are studies that use TAM, for example, to evaluate the use and acceptance of word processor [22], to verify perceptions of compatibility between systems [35], to evaluate emotional reactions to the use of computers [19], to evaluate the use of productivity packages [16] and to support software producers who want to check the demand for new ideas and products [15].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…In each constructor, items (or questions) are defined in order to measure them. The items were initially defined by Davis [13], [15], [37] but were later adapted by several authors according to the type of technology to be evaluated, as presented in the previous research [16]- [22], [24], [35], [36].…”
Section: Fig 2 Technology Acceptance Model Diagrammentioning
confidence: 99%
“…TRI has been used in many studies as an explanatory variable or as a moderator of a behavior, intention, or attitude. Pires, Costa Filho, and Cunha (2011) used TRI factors as differentiating elements between users and non-users of internet banking and found out that technology factors of optimism, security, and discomfort presented significant differences between users and non-users of internet banking; Nihat and Murat (2011) applied TRI to investigate technology acceptance in e-HRIM and found out that optimism and innovativeness positively influenced perceived usefulness and perceived ease of use but discomfort and insecurity did not have a positive effect on adoption of the system. TRI provides alternative perspectives and views on the adoption of and satisfaction with the technologies by identifying: the techno-ready users who champion and can influence adoption; the users who are thrilled about adoption but must be reassured of the benefits of adoption; and users who require strong conviction and proof of concept before they adopt.…”
Section: Technology Readiness Index (Tri)mentioning
confidence: 99%
“…However, the combination of the two models would not adequately solve the adoption challenges. For instance:(i) whereas TRI antecedents may correlate to DoI constructs, their combination does not take into account the mediating factors such as psychometrics characterization of users' behavioral intentions, (ii)a study by Pires et al (2011) found out that combining TRI and TAM led to only 3% increase in the intention to use technology, also a study by Godoe and Johansen (2012), found out that only optimism and innovativeness significantly affected perceived ease of use and perceived usefulness when TAM and TRIare combined, (iii) DOI variables of complexity and relative advantage are overlapping with TAM variables of perceived ease of use and perceived usefulness respectively (Carter &Bélanger, 2005) thus their combination may not provide a good prediction of adoption and use of technology. Therefore, the integration of the three models sought to solve the weaknesses of each model when applied independently or a combination of two models by focusing on innovation (DoI), perceptions (TAM), and readiness (TRI).…”
Section: Graphical Representation Of the Proposed Modelmentioning
confidence: 99%
“…A study done by Pires et al 36 uses TRI as antecedents of the acceptance model in measuring consumer acceptance on Internet banking in Brazil. It has concluded that TRI is beneficial in determining the level of consumer acceptance of IT innovations.…”
Section: Literature Reviewmentioning
confidence: 99%